If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(x + 5) = x + -4 + 5(3x + 2) Reorder the terms: -2(5 + x) = x + -4 + 5(3x + 2) (5 * -2 + x * -2) = x + -4 + 5(3x + 2) (-10 + -2x) = x + -4 + 5(3x + 2) Reorder the terms: -10 + -2x = x + -4 + 5(2 + 3x) -10 + -2x = x + -4 + (2 * 5 + 3x * 5) -10 + -2x = x + -4 + (10 + 15x) Reorder the terms: -10 + -2x = -4 + 10 + x + 15x Combine like terms: -4 + 10 = 6 -10 + -2x = 6 + x + 15x Combine like terms: x + 15x = 16x -10 + -2x = 6 + 16x Solving -10 + -2x = 6 + 16x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-16x' to each side of the equation. -10 + -2x + -16x = 6 + 16x + -16x Combine like terms: -2x + -16x = -18x -10 + -18x = 6 + 16x + -16x Combine like terms: 16x + -16x = 0 -10 + -18x = 6 + 0 -10 + -18x = 6 Add '10' to each side of the equation. -10 + 10 + -18x = 6 + 10 Combine like terms: -10 + 10 = 0 0 + -18x = 6 + 10 -18x = 6 + 10 Combine like terms: 6 + 10 = 16 -18x = 16 Divide each side by '-18'. x = -0.8888888889 Simplifying x = -0.8888888889
| 42+.99x=1.29x | | 49/56=x | | 7+2x-6+x= | | 3*x^2+10*x-8=0 | | ln(8x)=ln(6x^2) | | 4(3n+2)n=1 | | 3x-1+1=2 | | 9x+1=4x+2A | | 5+7q=-10+2q | | ln(8x)=2ln(6x) | | -x^2+6*x-8=0 | | -2(9v-4)+2v=2(v+7) | | x^2-9*x-22=0 | | 2x^2+8x+9= | | x^2+10x=2x-6 | | 7(9x+2)=8p | | -6(-4u+6)-2u=4(u-6)-6 | | X+2000=4x-1000 | | x^2-4*x+3=0 | | 3g+8=5g-20 | | 5(x-20)=3(x+30) | | 17x-6=3x+64 | | 4(x-2)-7x=7 | | x^2+12*x+20=0 | | 7.6X-2.2=54 | | 2(x+10)+3(x+20)=180 | | (11x+21)=(7x+33) | | x+(x+2)=790 | | -9(2)= | | 5(x+4)=3(x+20) | | 2x^2+20x-24=0 | | 2(x-7)=64 |